OPTIMIZATION OF DISCHARGE PLANNING FOR COVID-19 PATIENTS THROUGH INTEGRATED EDUCATION SYSTEM COVID NURSE ASSISTANT (CNA) TO PREVENT TRANSMISSION AND IMPROVING PATIENT SELF-CARE ABILITY IN RSSA - Evi Harwiati Ningrum; Ike Nesdia Rahmawati; Linda Wieke Noviyanti; Annisa Wuri Kartika; Ahmad Hasyim Wibisono; Ahsan Ahsan; Kuswantoro Rusca Putra (Caring : Jurnal Pengabdian Masyarakat, 2021)
The high number of COVID-19 cases was not balanced by the number of nurses assigned to the Covid isolation room with limited PPE availability. This causes many of the duties of nurses, especially health education, could not be performed completely. Thus, it is necessary to renew the Discharge Planning procedure for Covid 19 patients according to the characteristics of Covid-19 transmission. The purpose of this community service is to increase the effectiveness of the discharge planning for the COVID-19 patients to improve self-care and prevent infection transmission at home. This community service activity consists of 4 (four) stages, namely: 1) Preparation stage for coordination with the hospital; 2) Application development phase, consisting of application design, collection of educational media; 3) Implementation, launching and socialization of applications in the hospital environment; 4) Evaluation and monitoring stage. The results of the evaluation showed that as many as 58.7% of patients had used the CNA. About 62.7% patients experience an increase of their knowledge after accessing the CNA. There were 61.6% patients stated that the CNA had increased their knowledge on home care procedure post-Covid treatment. There are 62.3% of patients feel that the CNA supports patient care at home. The benefits of the CNA were expressed by 82 patients (87.2%) with increased self-care and as many as 76 patients (80.9%) stated that the CNA educational media was more attractive and easy to understand. The conclusion of this activity is that the CNA application can be implemented as a medium of health education for patients and families to improve their ability to take care of themselves.